Pengaruh Penggunaan Metode Active Learning Tipe Card Sort Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqih Di MTs PN 4 Medan - Nisa, Fadillatun (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
TheÂ  learning method is a method used by educators in the learning process to facilitate students in receiving learning material according to the objectives, the Active Learning Method is an alternative method that is used to increase the activity of student learning outcomes, especially by using the Card Sort type which is proven to be effective in facilitating students' understanding of the concepts being taught. The activeness of students in studying Fiqh is very important because Fiqh is a scientific discipline that studies Islamic rules and laws that must be obeyed. the existence of active learning for students, namely understanding the material taught by the teacher which is then manifested in everyday life. The active learning methodology encourages student participation during the teaching process so that students become more involved, creative, and able to express their own opinions about the material being taught. In this study, the active learning method was applied using card sort. The card sort type is a form of activity that involves students in the learning process, in the card sort type, students are asked to categorize a number of concepts or information into several related groups. The concept or information is usually written on small cards that students can arrange or arrange.